Предмет:
МатематикаАвтор:
аноним2(a + b)^-1 + (a^-2 + b^-2) / (a^-1 + b^-1) = 2 / (a + b) + (1 / a^2 + 1 / b^2) / (1 / a + 1 / b) = 2 / (a + b) + ((b^2 + a^2) / (a^2 * b^2) / (b + a) / (a * b)) = 2 / (a + b) + (b^2 + a^2) / (a^2 * b^2) * (a * b) / (b + a) = 2 / (a + b) + (b^2 + a^2) / ((a + b) * a * b) = (2ab + b^2 + a^2) / ((a + b) * a * b) = (a + b)^2 / ((a + b) * a * b) = (a + b) / (a * b).
Ответ: (a + b) / (a * b).
Автор:
tamiadeckerДобавить свой ответ
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть